Miriam Cooper papers - Cooper, Miriam, 1891-1976.
Correspondence, telegrams, writings, newspaper clippings, printed matter, and miscellany relating chiefly to Cooper's marriage to motion picture actor and director Raoul Walsh and her career in early motion pictures, especially her work with D.W. Griffith in "Birth of a Nation" and "Intolerance." Includes several telegrams from D.W. Griffith.
Actress; married film director Raoul Walsh.
Collection material in English.
Keywords: Walsh, Raoul, -- 1887-1980.; Griffith, D. W. -- 1875-1948.; Griffith, D. W. -- 1875-1948 -- Correspondence; Motion pictures; Acting; Birth of a nation (Motion picture); Intolerance (Motion picture); Actresses